2023
DOI: 10.18502/kss.v8i4.12965
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Health Services of The National Health Insurance Era in East Java - Indonesia: Barriers and Strategy

Abstract: The National Health Insurance ( JKN) system is designed to provide the availability of quality health services, but until now JKN participant have not felt the quality health care. The purpose of this study is to identify threats and weaknesses in health care quality control and formulate the implications of its strategy. The study was conducted at four Regional General Hospital (RSUD) in East Java - Indonesia, namely RSUD IbnuSina Gresik, RSUD NgudiWaluyoWlingiBlitar, RSUD dr. H. SlametMartodirdjoPamekasan, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This argument is supported by some studies. A study identified significant challenges in healthcare quality control in East Java, highlighting issues like delayed hospital claim payments, healthcare regulation and low public awareness of a healthy lifestyle, all of which affect the National Health Insurance (JKN) system (Wibowo et al ., 2023). And also impacted the hospital payment system in East Java and has the potential to increase fraud (Khoiri et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This argument is supported by some studies. A study identified significant challenges in healthcare quality control in East Java, highlighting issues like delayed hospital claim payments, healthcare regulation and low public awareness of a healthy lifestyle, all of which affect the National Health Insurance (JKN) system (Wibowo et al ., 2023). And also impacted the hospital payment system in East Java and has the potential to increase fraud (Khoiri et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%